Black Men Teaching in Urban Schools - Brockenbrough, Edward (Taylor & Francis, 2022)
This volume follows eleven Black male teachers from an urban, predominantly Black school district to reveal a complex set of identity politics and power dynamics that complicate these teachers’ relationships with students and fellow educators. It provides new and important insights into what it means to be a Black male teacher and suggests strategies for school districts, teacher preparation programs, researchers and other stakeholders to rethink why and how we recruit and train Black male teachers for urban K-12 classrooms.